Proceso De Atención De Enfermería En Paciente Adulto Con Dermatopolimiositis - Zambrano Vergara, Karen Katherine (2018)
Dermatopolimiositis is an inflammatory disease of the skin and skeletal muscles that is often associated with other connective tissue diseases, is associated with autoimmune diseases, can be confused very easily with other pathologies such as Systemic Lupus erythematosus, Dermatomyositis, Polymyositis, its etiology is still unknown. Estimated between 0.5 to 10 cases per 1 million of people in the United States, there is an increase between 10 and 15 years of age between children and between 45 and 60 years in adults, is presented more in women, by which affects both physical state and the mental state of the patient limiting the self-care that can be done by itself, being dependent on another person to carry out their activities. We can note that this pathology as is the Dermatopolimiositis is little known and through this clinical case we will introduce in the subject to improve our knowledge to give an attention with quality and warmth and the therapeutic regime in this type of disease is of great importance for the early recovery of the patient so we as health professionals should emphasize continue with the treatment to evidence good results.